PROTECTION OF INTERNATIONAL LAW OF TRADITIONAL SONGS AS TRADITIONAL CULTURAL EXPRESSIONS: A JURIDICAL ANALYSIS OF INDONESIA AND ITS PRACTICE - Muhammad Reyhan Zachary Asnawi; Ayu Riska Amalia (Mataram Journal of International Law, 2026)
This study examines the challenges of legal protection for Indonesian traditional songs as part of Traditional Cultural Expressions (TCEs). The main issue lies in the gap between the individualistic nature of the intellectual property (IP) legal framework and the communal characteristics of TCEs, which makes them vulnerable to unauthorized commercialization and claims by foreign parties. Using normative legal research methods through statutory, conceptual, case, and comparative approaches, this study aims to analyse forms of international and national legal protection and to identify challenges in their implementation in Indonesia. The findings indicate that the existing protection system remains inadequate. At the international level, conventional IP regimes are not aligned with the communal nature of TCEs. At the national level, the implementation of the Copyright Law and the Cultural Advancement Law is still constrained by the absence of specific implementing regulations and the lack of inter-agency synergy. This study recommends strengthening the regulatory framework through a sui generis system or stronger policy integration, as well as empowering indigenous communities as the primary custodians of cultural heritage.